Philosophical Publishing: Trying and Pushing the Boundaries. Antanas Rybelis interviewed by Aurimas Šukys - Šukys, Aurimas (Problemos, 2018)
[text in Lithuanian] Antanas Rybelis interviewed by Aurimas Šukys. Vilnius, March 20, 2009. Document: audiorecord (92 min.), privat collection of A. Šukys. Excerpt from the interview. Authorised by A. Rybelis (November 2018).